Populasi Penggerek Batang Padi pada Ekosistem Sawah Organik dan Sawah Anorganik - Hadi, Mochamad; Soesilohadi, RC Hidayat; Wagiman, FX; Soehardjono, Yayuk Rahayuningsih (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Rice stem borer (RSB ) is a major pest for rice in Central Java in the past ten years as well as previous years . The presence of RSB occurs during the rice growing season with a high intensity , especially in the rainy season . RSB which is the main type, yellow RSB Scirpophaga incertulas WalkerÂ and white S. innonata. Walker . Other types are pinkÂ Sesamia inferens Walker , striped Chilo suppressalis Walker, headed black C. polychrysus Meyrick , and shiny C. auricilius Dudgeon. Organic farming in Central Java is still not widely applied so it is still very less information available, including information on the fluctuations in species diversity and population abundance of RSB. In this study examined the types and abundance fluctuations keenekaragaman RSB populations in rice field ecosystem organic and inorganic. Research will be conducted for one year (3 times transplanting rice) paddy ecosystems in organic and inorganicÂ Bakalrejo Village, District Susukan, Semarang regency. The results showed that the dominant RSB is yellow S. incertulas. Yellow RSB found in every season paddy rice planting in both organic and inorganic rice. While the pink, shiny and white RSB, occasionally encountered. The RSB encountered seem to prefer the ecosystem tend rice paddy organic than inorganic . Keywords : rice stem borer ( RSB ) , organic rice ecosystem, inorganic rice ecosystem.